RELATIONSHIP OF AGE, PARITY AND BIRTH WEIGHT WITH A RUPTURE OF THE PERINEUM OF MATERNAL AT PMB - haria, paula; Wigati, Putri Wahyu; Saidah, Halimatus (Universitas Kadiri, 2021)
Maternal Mortality Rate is one indicator of the quality of maternal health services in a country. Preliminary study at PMB Ny.